Hysterotomy for Management of Dystocia due to Prepartum Vagino-Cervical Prolapse Coupled with Vaginal Tear in a Jersey Crossbred Cow - Sarath, Thulasiraman; Rangasamy, Seerangan; Arunmozhi, Narayanasamy; Kumar, Raju Suresh; Pugazharasi, Chidambaram (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Vagino-cervical prolapse is a common reproductive disorder of ruminants, usually seen in pluriparous cows in late gestation and occasionally after parturition (Noakes et al., 2019). It is mainly seen in ruminants, rare in other species, and usually involves protrusion of the floor, the lateral walls, and a portion of the roof of the vagina through the vulva with the cervix and uterus moving caudally (Roberts, 2004). Predisposing factors include hereditary factors in some cattle breeds, increased intra-abdominal pressure, intra-abdominal fat or rum n distention, softening of the pelvic ligaments, bacterial or fungal infections, hormonal imbalance, hypocalcemia, mineral deficiency, and feed containing phyto estrogens like clover, soybean meal, etc. (Roberts, 2004; Miesner and Anderson, 2008). Highconcentration of estrogen secreted by the placenta in the last trimester of pregnancy causes relaxation of the vulva, vulvar sphincter muscles, pelvic ligaments, and adjacent structures, leading to vagino-cervical prolapse in cows (Roberts, 2004; Wolfe, 2009). A combination of increased estrogen with decreased progesterone and production of relaxin, especially in the last two weeks of gestation, may cause relaxation of the pelvic ligaments and surrounding soft tissues (Henricks et al., 2011). The present paper reports a rare case of dystocia due to prepartum vagino-cervical prolapse coupled with a vaginal tear in a Jersey crossbred cow and its successful delivery through hysterotomy.